2021
DOI: 10.7759/cureus.15962
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hyperinflation of an Intragastric Balloon Causing Gastric Outlet Obstruction

Abstract: A 39-year-old female with a history of obesity (body mass index, BMI = 33.6) had an intragastric balloon (IGB) placed in February 2020 for weight loss. She presented with gastric outlet obstruction after a delay in the removal of her IGB because of the coronavirus disease (COVID) pandemic. Although uncommon, spontaneous hyperinflation of IGBs has been reported and the US FDA also has issued a warning regarding the risk of spontaneous hyperinflation. The etiology of the hyperinflation is unclear, however, gas-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Bomman et al described a case of a patient who did not present to follow-up for IGB removal after 6 months of placement due to the COVID-19 pandemic restrictions. 8 Basile et al reported a case of GOO 6 months after placement of an IGB which had spontaneously doubled its size 9 and De Quadros et al described an acute abdomen with GOO due to IGB hyperinflation 3 months after placement. 7 In contrast to our case, these cases occurred with IGBs which required endoscopic retrieval after 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bomman et al described a case of a patient who did not present to follow-up for IGB removal after 6 months of placement due to the COVID-19 pandemic restrictions. 8 Basile et al reported a case of GOO 6 months after placement of an IGB which had spontaneously doubled its size 9 and De Quadros et al described an acute abdomen with GOO due to IGB hyperinflation 3 months after placement. 7 In contrast to our case, these cases occurred with IGBs which required endoscopic retrieval after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Bomman et al. described a case of a patient who did not present to follow‐up for IGB removal after 6 months of placement due to the COVID‐19 pandemic restrictions 8 . Basile et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying mechanism is yet to be identified, although balloon permeability or gas-producing infectious microorganisms [ 11 ] have been evoked in some cases. Hyperinflated balloons can be discovered incidentally at the time of the scheduled balloon removal if asymptomatic [ 10 ] or can present with gastric outlet obstruction [ 12 ]. If left in place, gastric volvulus [ 13 ] or necrosis [ 14 ] may result.…”
Section: Discussionmentioning
confidence: 99%